Rhetorical Structure of University Promotional Brochures Written by Indonesians at Undergraduate and Graduate Programs - Kurniawan, Iwan; Irawansyah (ETERNAL (English Teaching Journal), 2025)
The purposes of this research were to know the rhetorical structures of university brochures of undergraduate and graduate program and the differences of them in term of moves and steps. This research was qualitative and quantitative in nature; in other words, it employed mixed method.  Qualitative data was taken in the forms of university brochures communicative purposes narrations, whereas quantitative data in the form of move and step frequency and percentage. The rhetorical structure are as follows: service Provider Overview, presenting academic service, Internationalism, presenting university achievement, presenting student life, Presenting the location of the service, Validating the effectiveness of service provided, Special notes. From those moves and steps structures, all the moves proposed by Barabas are found where service provider, presenting academic, presenting students life, presenting service location, and special notes are 100% obligatory for undergraduate level; service provider, presenting academic, special notes are 100% obligatory. For steps, university names, university emblems, university departments, academic programs, procedure applications, contact information are 100% obligatory in undergraduate and university names, university emblems, brochure titles, university departments, academic programs are 100% obligatory. The differences between undergraduate and graduate promotional brochures are on the move of validating the effectiveness of service provided, from steps numbers on respective moves, the status obligatory or optional of moves and steps.